2021
DOI: 10.1016/j.dark.2021.100804
|View full text |Cite
|
Sign up to set email alerts
|

Late-time acceleration with a scalar field source: Observational constraints and statefinder diagnostics

Abstract: This article discusses a dark energy cosmological model in the standard theory of gravity -general relativity with a broad scalar field as a source. Exact solutions of Einstein's field equations are derived by considering a particular form of deceleration parameter q, which shows a smooth transition from decelerated to accelerated phase in the evolution of the universe. The external datasets such as Hubble (H(z)) datasets, Supernovae (SN) datasets, and Baryonic Acoustic Oscillation (BAO) datasets are used for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…Additionally, this article is an attempt to design a cosmic model by taking a suitable parametrization of the deceleration parameter, which was first considered in the paper [88] wherein two phenomena Big Rip and Big Bang of the Universe were discussed together with the cosmic evolution in the general theory of relativity. Later on, the same model is studied in the paper [94] where the authors found some observational constraints using some external datasets and also discussed the statefinder diagnostics. Here, in our study, we have taken the motivation from [88] and [94] and extended the study in f (R, T ) gravity wherein our main intention is to study the physical parameters (especially EoS ω) in f (R, T ) gravity with quadratic correction terms i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, this article is an attempt to design a cosmic model by taking a suitable parametrization of the deceleration parameter, which was first considered in the paper [88] wherein two phenomena Big Rip and Big Bang of the Universe were discussed together with the cosmic evolution in the general theory of relativity. Later on, the same model is studied in the paper [94] where the authors found some observational constraints using some external datasets and also discussed the statefinder diagnostics. Here, in our study, we have taken the motivation from [88] and [94] and extended the study in f (R, T ) gravity wherein our main intention is to study the physical parameters (especially EoS ω) in f (R, T ) gravity with quadratic correction terms i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, the same model is studied in the paper [94] where the authors found some observational constraints using some external datasets and also discussed the statefinder diagnostics. Here, in our study, we have taken the motivation from [88] and [94] and extended the study in f (R, T ) gravity wherein our main intention is to study the physical parameters (especially EoS ω) in f (R, T ) gravity with quadratic correction terms i.e. f (R, T ) = R + αR 2 + 2λT .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus we are at very large distance ( ∼ at infinite distance) from an event occurred in the beginning of the universe. The statefinder diagnostic is a valuable tool in current cosmology used to differentiate various dark energy models [100][101][102][103]. Different trajectories in the (r − s) (r − q) and (s − q) planes express the time evolution for various dark energy models.…”
Section: Particle Horizonmentioning
confidence: 99%
“…The cosmography is the study of scale factor by expanding it by Taylor series with respect to the cosmic time. The cosmographical parameter like jerk (J), snap (S), and lerk (L) parameters are [91][92][93][94]…”
Section: Evolutions Of Cosmological and Cosmographical Parametersmentioning
confidence: 99%